Konsep Manusia dalam Dayak Benuaq Ditinjau dalam Pemikiran Heidegger - Sipriadi, Ambrosius; Riyanto, Armada (Universitas Insan Budi Utomo, 2024)
In this paper, the author tries to connect the concept of human in the context of Dayak Benuaq culture by referring to Martin Heidegger's philosophical thoughts about human existence. The literature method is used by the author in this paper. This paper explains Heidegger's concept that highlights human existence in the world and relates this concept to the Dayak Benuaq view of humans as an inseparable part of nature and their environment. In addition, this paper examines the relationship between the everyday human experience in Heidegger's thought with the practices and philosophical meanings that the Dayak Benuaq people may have. In the context of time, Heidegger emphasizes the importance of the dimension of time in human understanding. This paper tries to understand how time is viewed in the life of the Benuaq Dayak, especially in relation to the spiritual aspect and the continuous cycle of life. Although Heidegger does not directly discuss Dayak Benuaq culture or society, this paper relates his philosophical or spiritual principles to the concept of man in the context of Dayak Benuaq culture. This paper aims to present a new perspective in understanding the concept of human, especially for the Dayak Benuaq people. The author also finds similarities between the concept of man in Dayak Benuaq culture and Heidegger's concept of man, especially in Attachment to Nature and the Environment, Existence in Daily Life, and the Experience of Time